Literatura piękna w etyce - GŁĄB, Anna (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
The article undertakes the consideration of the relation between literary fiction and ethics in the philosophical output of Tadeusz Styczeń, SDS. The problem in question is approached from a broader perspective encompassing the relations between literature and philosophy in general. Against this background, the author discusses the inspiration Styczeń drew from literature for the development of his ethics and for his approach to communicating it. Apart from presenting particular instances of Styczeń’s reference to literary fiction in his ethics, the author considers two aspects of the relation between literature and ethics in his work, namely, the relevance of this relation for him in constructing and teaching moral philosophy and his reference to instances of literary fiction that would ensure that the conclusions thus formulated, while not being necessary truths, would retain the status of rational statements in ethical discourse. As far as the first aspect is concerned, the author’s attention is focused on the first−person narration, so significant in communicating ethics. The author also considers the possibility of complementing the shortcomings of an ethical theory by literary fiction. As far as the second aspect of the present considerations is concerned, the author refers to particular instances in which Styczeń combined poetry with ethical discourse and stresses the significance of enthymematic statements for moral philosophy. Translated by Dorota Chabrajska